A Juridical Analysis of Artificial Intelligence Misuse for the Sexual Exploitation of Women’s Photo on Platform X Under Indonesia Positive Law - Rhesas Shalatan; Mega Fitri Hertini (Locus: Jurnal Konsep Ilmu Hukum, 2026)
This article aims to analyze the misuse of Artificial Intelligence (AI) on platform X for the sexual exploitation of women's photos and assess the effectiveness of Indonesian positive law in providing protection. This article applies a juridical-normative method through a statute approach to examine regulations related to the misuse of AI. The results of the study indicate that positive legal frameworks such as the 1945 Constitution, the Criminal Code, the Pornography Law, the ITE Law, the PDP Law, and the TPKS Law can be used to address the misuse of AI for sexually suggestive photo manipulation. However, all of these regulations do not specifically and explicitly regulate AI-based technology crimes, so law enforcement still relies on broadening the interpretation of the offense. Therefore, there is a need for more specific and adaptive regulatory updates to AI developments and increased responsibility of digital platforms in preventing the misuse of AI-based technology.